Preventing cholera in India: Synthesizing evidences through a systematic review for policy discussion on the use of oral cholera vaccine. (29th February 2020) - Panda, Samiran; Chatterjee, Pranab; Deb, Alok; Kanungo, Suman; Dutta, Shanta
Abstract: Development of oral cholera vaccines (OCVs) experienced exciting times over the last two decades. A two-dose OCV, found efficacious through field trials, has obtained license for use in India. However, the current policy discussion revolves around 'to use or not to use' this vaccine covering entire population in the country, which has its own cost implications. We conducted a systematic review to address this conundrum. The disease burden and distribution, potential impact, programmatic issues, and competing priorities were kept in consideration. Peer reviewed articles and 'Integrated Disease Surveillance Program' data, generated by Government of India, were accessed. Our synthesis highlights that cholera burden estimates for India have been hamstrung by their extrapolation from a single incidence study conducted in Kolkata. Heterogeneity of 685 Indian districts regarding vulnerability to cholera is also obvious. Analysis of outbreak reports indicated that some settlements and sub-populations were more vulnerable to diarrhea/cholera than others. Infrastructure failure leading to contamination of drinking water and behavioral issues were of concern. Investment in safe water, sanitation and hygiene (WASH) and addressing inequity of health services pertaining to vulnerable population groups are the needs of the hour. OCV could play an important role as one of the elements in such multi-component cholera prevention effort. OCV administration through public health system in Odisha identified logistic challenges, with low uptake of the second dose at 46%, while 61% of the target population received the first dose. We identified accumulating global evidence on the advantage and efficacy of single-dose based approach, where the same OCV, as licensed in India, was used. The short-lasting nature of cholera outbreaks in India also argue in favor of such pragmatism. Failure to implement multi-component prevention strategy today runs the risk of perpetuating inequity, recurring cholera outbreaks in future, and its retinue of costs.